Artificial condition - Wells, Martha (Wells, Martha. Murderbot diaries ;, 2018)
It has a dark past - one in which a number of humans were killed. A past that caused it to christen itself Murderbot. But it has only vague memories of the massacre that spawned that title, and it wants to know more. Teaming up with a research transport vessal named ART (you don't want to know what the A stands for), Murderbot heads to the mining facility where it went rogue. What it discovers will forever change the way it thinks ...